“I am annoyed”: of the Digital Feedback Feature on the ELSA Speak Application - Aulyzana, Warda Fatima; Hudori, Rizki Febri Andika (P3M Politeknik Negeri Jember, 2025)
Pronunciation plays a crucial role in effective communication, yet it can be difficult for non-native English speakers due to the complexities of articulating English words. The wide range and complexity of English vowel sounds frequently pose significant challenges for learners. Nevertheless, technological improvements provide useful resources for enhancing English pronunciation, with applications like ELSA Speak serving as effective tools for students to fine-tune their pronunciation skills. This study sought to explore the experiences of undergraduate students with the digital feedback offered by ELSA Speak in relation to pronunciation learning, utilizing a qualitative descriptive methodology. The research was organized around a qualitative descriptive framework and incorporated thematic analysis, featuring a sample of three undergraduate students from the University of Jember. Findings from the data revealed that students encountered diverse experiences with the digital feedback functionality of ELSA Speak, which included instruction on accurate word pronunciation and the provision of instant feedback regarding their pronunciation efforts. Additionally, this digital feedback mechanism offered students three primary types of exercises: pronunciation, intonation, and conversation practice, thereby facilitating enhanced learning and improvement in their pronunciation skills. However, students had issues with the free version of ELSA Speak, claiming the inability to use certain activities due to the obligation to pay for access to the premium edition.